Switching anti-EGFR antibody re-sensitizes head and neck cancer patient following acquired resistance to cetuximab - Khattri A.; Sheikh N.; Agrawal N.; Kaushik S.; Kochanny S.; Ginat D.; Lingen M.W.; Blair E.; Seiwert T.Y. (My University, 2025)
Cetuximab induces responses in about 13% of head and neck squamous cell carcinomas (HNSCC). We describe the molecular mechanism of acquired resistance to cetuximab, which could be overcome by switching to a different anti-EGFR antibody. Biopsies were collected at three different time points: before the start of cetuximab (PRE-cetux), at acquired resistance to cetuximab (AR-cetux), and at acquired resistance to duligotuzumab (AR-duligo). Biopsies were analyzed using tumor and normal whole-exome sequencing, RNASeq, and targeted panel sequencing with ultra-deep coverage to generate differential mutation and expression profiles. WES and targeted sequencing analysis identified an EGFR p.G465R extracellular domain mutation in AR-cetux biopsy. Furthermore, RNASeq confirmed the expression of this mutation in the tumor tissue. This mutation prevented the binding of cetuximab to EGFR and was not present in PRE-cetux and AR-duligo biopsies, suggesting a potential mechanism of acquired resistance to cetuximab. Molecular dynamic simulations confirmed that duligotuzumab effectively binds EGFR with a p.G465R mutation. Interestingly, the p.G465R mutation improved the stability of the duligotuzumab-EGFR complex as compared to the wild-type EGFR. This is the first report of an EGFR ECD mutation associated with acquired resistance to cetuximab, posing a need for further validation. We suggest appropriate serial mutational profiling to identify ECD mutations should be considered for select patients with initial cetuximab benefit. © The Author(s), under exclusive licence to Springer Nature America, Inc. 2024.